S-11=(-34)

Simple and best practice solution for S-11=(-34) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for S-11=(-34) equation:


Simplifying
S + -11 = (-34)

Reorder the terms:
-11 + S = (-34)
-11 + S = -34

Solving
-11 + S = -34

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + S = -34 + 11

Combine like terms: -11 + 11 = 0
0 + S = -34 + 11
S = -34 + 11

Combine like terms: -34 + 11 = -23
S = -23

Simplifying
S = -23

See similar equations:

| (z^2-2iz)*(z^2+25)=0 | | 3x+3=-25 | | -11=s+5 | | (-11)=13+x | | 15/25=y/30 | | (-15)+g=(-5) | | (2c+9)(c+5)= | | f(x)=6x^3+8x^2+3 | | 6(1-2x)-x=-46 | | B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 | | M+(-10)=(-2) | | -3a+8=2 | | 4x-3y=52 | | (-17)=(-9)+q | | f(x)=a^3-3a^2-9 | | 2.25=3/4(b-5) | | 17+n=4 | | 6x-x^2+16= | | (-22)+j=(-24) | | 72.8=7(m+3.1) | | 4x+23=75 | | (2c+9)x(c+5)= | | 3[m-1.2]=9 | | h-8+2(h-8)=72 | | 47=19-4x | | 39+x=30+2x | | R-20+4=18 | | 1521=39p+390 | | M+52=53 |

Equations solver categories